Impact of demographic and loan size on the probabilities of women freedom of movement empowerment - Yasmeen, Kausar; Abd Karim, Mohd Zaini (Macrothink Institute, 2014)
The purpose of this paper is to evaluate the impact of microfinance involvement of women’s freedom of movement empowerment.The cross sectional data for this study is collected by using questionnaires.Using random sampling, 744 households are selected from female clients of Khushhali Bank and National Rural Support Program from three districts namely district Bahawalpur, District Bahawalnagar and district Rahim Yar Kan of Division Bahawalpur, Pakistan.We used the multinomial logit model.The loan size increases women’s freedom of movement empowerment.This paper is intended to be a valuable contribution in term of socio- economic and political arena.This paper recommends that the future research should be done in other province of Pakistan, as there is cultural difference between Punjab, Sarhad and Baluchistan. In addition, the future research can examine the impact of socio cultural factors.